Medication errors and contributing factors at ward, supply pharmacy, Hospital Tengku Ampuan Rahimah Klang - Shahruden, Ahmad Syakir; Afendy, Tasnym; Amir Hamzah, Mohd Firdaus (2018)
Medication error is an error in prescribing, dispensing or administering of drug, irrespective of whether such errors lead to adverse consequences or not [1]. It is also known as any error occurring in the medication-use process such as writing a medication orders, preparing and dispensing medication or administration of medication. The study was carried out to investigate the total medication error detected while dispensing, the types of medication error occur, the type of personnel involved, the factors contributing, and preventive measure taken to reduce medication error at Ward Supply Pharmacy Department, Hospital Tengku Ampuan Rahimah, Klang. The QAP 1 A & 1 B: Daily Recording of Error Detected before Dispensing and Factors Contributing form used to collect data related to any errors detected while counterchecking and factors contributing to errors detected before dispensing medication to the patients. The information in the QAP 1A & 1 B will be summaries and reported in QAP 1 form and SIQ QAP report form for analysing purpose every month. The purpose of this study case is to measure, and monitor incidence of errors occur during medication preparation process besides ensure correct dispensing of medication to the right patient as prescribed. Based on the study carried on October to December 2017, it showed that the error that mostly occurs during this time period is wrong quantity. Other than that, trainees commit more mistakes during the medication preparation processes than pharmacists and pharmacy assistants. Finally, human factor has high number on factor contributing to medication error.